2015
DOI: 10.2527/jas.2015-8952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy on sexual maturation and sperm production in Holstein bulls1

Abstract: In prepubertal bulls and heifers of dairy and beef breeds, puberty can be induced to occur earlier than typical with targeted high-energy diets due to precocious activation of the endocrine mechanisms that regulate puberty. Precocious activation of puberty in bulls intended for use in the AI industry has the potential to hasten and perhaps increase sperm production. It was hypothesized that feeding bulls a high-energy diet beginning at 8 wk of age would advance the prepubertal rise in LH and lead to advanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Although the response of age at puberty onset to early life dietary manipulation has been reported previously in bulls (Brito et al, 2007c;Dance et al, 2015;Harstine et al, 2015), this is the first study using dairy bulls to report that effects of a reduction in ADG during early life cannot be overcome through subsequent realimentation. In agreement with the findings of the current study, Brito et al (2007a) reported that the delay in puberty caused by restricting Angus and Angus × Charolais bulls from 10 to 26 wk could not be overcome by offering ad libitum concentrate after 26 wk of age, following a restricted diet (75% of the intake of ad libitum fed controls) in early life.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Although the response of age at puberty onset to early life dietary manipulation has been reported previously in bulls (Brito et al, 2007c;Dance et al, 2015;Harstine et al, 2015), this is the first study using dairy bulls to report that effects of a reduction in ADG during early life cannot be overcome through subsequent realimentation. In agreement with the findings of the current study, Brito et al (2007a) reported that the delay in puberty caused by restricting Angus and Angus × Charolais bulls from 10 to 26 wk could not be overcome by offering ad libitum concentrate after 26 wk of age, following a restricted diet (75% of the intake of ad libitum fed controls) in early life.…”
mentioning
confidence: 67%
“…However, the reproductive potential of these young bulls is limited by the quantity and quality of semen that they can produce (Rawlings et al, 2008). Recent studies have reported that enhanced nutrition before 31 wk of age leads to earlier onset of puberty in Holstein-Friesian bulls (Dance et al, 2015;Harstine et al, 2015), whereas restricting the diet of beef bulls before 26 wk of age delays age at puberty onset, which could not be reversed by an increase in the plane of nutrition from 27 wk to 70 wk of age (Brito et al, 2007a). In both studies conducted on Holstein-Friesian bulls (Dance et al, 2015;Harstine et al, 2015), postpubertal semen production was unaffected by diet, whereas a high plane of nutrition from 10 to 30 wk in young beef bulls led to higher total daily sperm production at 74 wk of age compared with those offered a control diet from 10 to 74 wk of age (Brito et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, evidence indicated that nutrition can influence male reproduction. For example, Holstein bulls fed high-energy diet showed advanced testicular maturation 26 . In mature male sheep and goats, changes in feed intake can induce changes in the size of the seminiferous tubules and spermatogenic efficiency 1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these bulls cannot produce ejaculates of sufficient quality for cryopreservation until they are greater than 1 year of age (Murphy et al 2018) and demand for their semen often far exceeds supply. Hastening the onset of puberty and subsequent sexual maturation would therefore benefit the industry and make high-quality semen available at a younger age (Harstine et al 2015).…”
Section: Introductionmentioning
confidence: 99%